HEALTH CONDITION OF OLDER PEOPLE AND MEDICAL FOLLOW-UP IN THE PRIMARY HEALTH CARE - Aniozova, D.J.; Ismailova, K.S. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
to study the morbidity of older people and the provision of primary health care to them in selected regions of Uzbekistan. Material and methods: selectively in 6 districts of 6 regions of Uzbekistan and in Tashkent city, a survey (survey) of 365 people 60 years and older living in households was conducted. For the survey used a specially designed questionnaire; data copying was carried out in the developed clinical map. Results: every second respondent noted the presence of chronic diseases (2 on average), while the lonely and single living spouses had an average of 3 diseases. The deficiencies of the patronage service are revealed, which may be due to the lack of standards for individual nosologies. The inconsistency in the provision of medical and social assistance was also identified. Conclusions: the lack of national standards for the management of elderly patients, taking into account the presence of several chronic diseases and the provision of medical and social care at the primary level, insufficient time for taking a doctor, the lack of integration of medical and social care reduces the quality of medical care provided to the elderly population